Odpowiedzi

2010-03-10T20:30:12+01:00
{ x+y=9
{ x-y=3
__________
2x = 12
x = 6
podstawiamy do pierwszego { x+y=9
6+y = 9
y = 3


{x+4y=11 /*(-2)
{2x+5y=10

-2x-8 y= -22
2x+5y=10
____________
-3y = -12 /:(-3)
y = 4
podstawiamy tu: {x+4y=11
x + 4*4 = 11
x +16 = 11
x = -5
2010-03-10T20:31:51+01:00
A)
{ x+y=9 /
{ x-y=3 / +

{ 2x = 12 /:2
{ x + y = 9

{ x = 6
{ 6 + y = 9

{x = 6
{y = 9 - 6

{x = 6
{y = 3

b)
{x+4y=11 /x(-2)
{2x+5y=10

{-2x - 8y = -22 /
{2x + 5y = 10 / +

{- 3y = - 12 / : (-3)
{x + 4y = 11

{ y = 4
{ x + 16 = 11

{ y = 4
{ x = -5


2010-03-10T20:32:03+01:00
1]
x+y=9/×(-1)
x-y=3

-x-y=-9
x-y=3

-2y=-6
y=-6:-2
y=3

x+3=9
x=9-3
x=6
spr. 6+3=9
9=9

6-3=3
3=3
b]
x+4=11/×(-2)
2x+5y=10

-2x-8y=-22
2x+5y=10

-3y=-12
y=-12:-3
y=4

x+4×4=11
x=11-16
x=-5
spr.-5+4×4=11
-5+16=11
11=11

2×-5+5×4=10
-10+20=10
10=10